-2(2x-3)-(2x-6)+5=-5(x-1)-(2x+6)+3

Simple and best practice solution for -2(2x-3)-(2x-6)+5=-5(x-1)-(2x+6)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2x-3)-(2x-6)+5=-5(x-1)-(2x+6)+3 equation:


Simplifying
-2(2x + -3) + -1(2x + -6) + 5 = -5(x + -1) + -1(2x + 6) + 3

Reorder the terms:
-2(-3 + 2x) + -1(2x + -6) + 5 = -5(x + -1) + -1(2x + 6) + 3
(-3 * -2 + 2x * -2) + -1(2x + -6) + 5 = -5(x + -1) + -1(2x + 6) + 3
(6 + -4x) + -1(2x + -6) + 5 = -5(x + -1) + -1(2x + 6) + 3

Reorder the terms:
6 + -4x + -1(-6 + 2x) + 5 = -5(x + -1) + -1(2x + 6) + 3
6 + -4x + (-6 * -1 + 2x * -1) + 5 = -5(x + -1) + -1(2x + 6) + 3
6 + -4x + (6 + -2x) + 5 = -5(x + -1) + -1(2x + 6) + 3

Reorder the terms:
6 + 6 + 5 + -4x + -2x = -5(x + -1) + -1(2x + 6) + 3

Combine like terms: 6 + 6 = 12
12 + 5 + -4x + -2x = -5(x + -1) + -1(2x + 6) + 3

Combine like terms: 12 + 5 = 17
17 + -4x + -2x = -5(x + -1) + -1(2x + 6) + 3

Combine like terms: -4x + -2x = -6x
17 + -6x = -5(x + -1) + -1(2x + 6) + 3

Reorder the terms:
17 + -6x = -5(-1 + x) + -1(2x + 6) + 3
17 + -6x = (-1 * -5 + x * -5) + -1(2x + 6) + 3
17 + -6x = (5 + -5x) + -1(2x + 6) + 3

Reorder the terms:
17 + -6x = 5 + -5x + -1(6 + 2x) + 3
17 + -6x = 5 + -5x + (6 * -1 + 2x * -1) + 3
17 + -6x = 5 + -5x + (-6 + -2x) + 3

Reorder the terms:
17 + -6x = 5 + -6 + 3 + -5x + -2x

Combine like terms: 5 + -6 = -1
17 + -6x = -1 + 3 + -5x + -2x

Combine like terms: -1 + 3 = 2
17 + -6x = 2 + -5x + -2x

Combine like terms: -5x + -2x = -7x
17 + -6x = 2 + -7x

Solving
17 + -6x = 2 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
17 + -6x + 7x = 2 + -7x + 7x

Combine like terms: -6x + 7x = 1x
17 + 1x = 2 + -7x + 7x

Combine like terms: -7x + 7x = 0
17 + 1x = 2 + 0
17 + 1x = 2

Add '-17' to each side of the equation.
17 + -17 + 1x = 2 + -17

Combine like terms: 17 + -17 = 0
0 + 1x = 2 + -17
1x = 2 + -17

Combine like terms: 2 + -17 = -15
1x = -15

Divide each side by '1'.
x = -15

Simplifying
x = -15

See similar equations:

| y=-4x-31 | | a=5-9a+8 | | 6x+8y-2x-y= | | 3/4=87*9 | | 7x-12-2x=7x-9 | | (x-1)+(2x+3)+(2x+3)=180 | | 9=87/3/4 | | 15x-.75=13x-.50 | | 87=3/4/9 | | 15x/2+19=12x+7/2 | | 14/19/11 | | 9x^4-10x^2+1=0 | | 1(t-3)+7t=4(2t+4)-13 | | x=0.40(x+15) | | 76c=828 | | y-5=-1/8x | | 7x+3y=5 | | 196*47/49*1/16 | | p-r=c | | 20+15x/2=21 | | 2(5-n)=-25 | | 5/7x=30 | | x+2x+2=10 | | 5/2+5/2y=2y-4 | | 6-2(3x-5)=-8 | | 14+8x=55 | | w=-r | | 12x-170=4x-10 | | 11x-2(x-7)=9(x+1)+7 | | a^2-13a+22=0 | | 7t=4*49 | | 5-9x=-173 |

Equations solver categories